Testing in Xcode : unit testing, UI testing, and code coverage - Mårtensson, Bill (Apress, 2019)
"Learn automatic testing in Xcode. Start by creating a simple test app that intentionally crashes in given scenarios. Then review the code to find obvious bad practices and issues. Discover why unit testing is important and perform a simple unit test. Work with test cases before adding functionality. Then increase code coverage and learn why it's important. Finally work with different parts of the app to test specific functionality."--Resource description page